Exploring universal basic income a guide to navigating concepts, evidence, and practices - Gentilini, Ugo; Grosh, Margaret; Rigolini, Jamele; Yemtsov, Ruslan (World Bank Group, 2020)
"Universal Basic Income (UBI) is one of the most hotly-debated ideas in development and social protection. Drawing from global evidence and experiences, this volume provides a compass to help navigate key issues and trade-offs, as well as offering new data and insights to better inform choices around the appropriateness and feasibility of UBI in different contexts. Structured around seven chapters and based on one of the most comprehensive reviews of the literature available, the book provides a framework to understand the interplay between objectives, design, incentives, micro-simulations, financing, political economy, and implementation of UBI as well as of social assistance more generally"--
Keywords: Garantiertes Mindesteinkommen